Cross-Activation of Hemichannels/Gap Junctions and Immunoglobulin-Like Domains in Innate–Adaptive Immune Responses - Meng, Jiang-Hui; Chen, Chang-Xu; Ahmadian, Mohammad R.; Zan, Hong; Luo, Kai-Jun; Jiang, Jean X. (Frontiers in Immunology, 2022)
Hemichannels (HCs) and Ig-like domain-containing proteins (IGLDCPs) are in-volved in the innate–adaptive immune response independently. Despite the evident demonstrating the importance of HCs and IGLDCPs in initiating, implementing, and terminating the entire immune response, our understanding of their mutual interactions in immunological function remains rudimentary. IGLDCPs include immune checkpoint molecules of the immunoglobulin family expressed in T and B lymphocytes, most of which are cluster of differentiation (CD) antigens. They also constitute the principal components of the immunological synapse (IS), which is formed on the cell surface, including the phagocytic synapse, T cell IS, B cell IS, and neural synapse. During the three stages of the immune response, namely innate immunity, innate–adaptive immuni-ty, and adaptive immunity, HCs and IGLDCPs are cross-activated during the entire pro-cess. We have attempted to summarize our current understanding of HC-released im-mune signaling factors that influence IGLDCPs in regulating innate–adaptive immunity through our review. ATP-induced “eat me” signals released by HCs, as well as CD31, CD47, and CD46 “don’t eat me” signaling molecules, cause robust initiation of innate immunity, which serves to regulate phagocytosis. Additionally, HC-mediated trogocyto-sis promotes antigen presentation and amplification. Importantly, HC-mediated CD4+ T lymphocyte activation is critical in the transition of the innate immune response to adap-tive immunity. HCs also mediate non-specific transcytosis of antibodies produced by mature B lymphocytes, for instance, IgA transcytosis in ovarian cancer cells, which triggers innate immunity. Further understanding of the interplay between HCs and IG-LDCPs would aid in identifying therapeutic targets that regulate the HC–Ig-like domain immune response, thereby providing a viable treatment strategy for immunological dis-eases. The present review delineates the clinical immunology-related applications of HC–Ig-like domain cross-activation, which would greatly benefit medical professionals and immunological researchers alike.